Mental Comorbidity in Rheumatic Diseases - Seifert, Olga; Baerwald, Christoph (Aktuelle Rheumatologie, 2021)
In this review, we summarise the most relevant studies in a PubMed Search term “mental disorders and rheumatic disease” in the last 15 years. Mental disorders such as depression and anxiety are common in people with rheumatic diseases. Treating these comorbidities can improve the patientʼs quality of life. The high prevalence of symptoms of psychiatric disorders is a challenge for rheumatologists, especially with regard to the differentiation of possible psychiatric components in rheumatological diseases. Screening for psychiatric problems in patients with rheumatic diseases should be evaluated as soon as possible, as these can have a major influence on the perception of pain and physical functioning status from the outset. Mental health disorders are seen as a risk factor for poor patient outcomes, as patients may not adhere to medical treatments. The potential side effects of biological agents can increase patient anxiety and affect adherence to therapy. Therefore, interdisciplinary care would be of great advantage in the treatment of rheumatic patients with psychological comorbidities.
Keywords: depression; anxiety; bipolar disorder; schizophrenia; DMARDs